Retention behavior of isomeric triacylglycerols in silver-ion HPLC: effects of mobile phase composition and temperature - Lísa, Miroslav; Denev, Rumen; Holčapek, Michal (Journal of separation science, 2013)
A systematic study of the retention behavior of isomeric triacylglycerols (TGs) in silver-ion HPLC on a ChromSpher Lipids column has been performed between 10 to 40°C using the most widespread hexane- and dichloromethane-based mobile phases. The randomization of mono-acyl TG standards and the random esterification of glycerol with fatty acids are employed to produce mixtures of TG isomers. The mobile phase composition has no influence on the general retention pattern, but significant differences in the retention order of double bond (DB) positional isomers in hexane and dichloromethane mobile phases are described and compared with the previous literature data. Saturated TGs with fatty acyl chain length from C7:0 to C22:0 are partially separated using the hexane mobile phase but not at all with the dichloromethane mobile phase. The hexane mobile phase enables at least partial resolution of TG regioisomers with up to seven DBs, while the resolution of only ALA/AAL and ALnA/AALn isomers is achieved with the dichloromethane mobile phase. The effect of temperature differs significantly depending on the mobile phase composition. Retention times of TGs increase with increasing temperature in the hexane mobile phase, while an opposite effect is observed for the dichloromethane mobile phase.
Keywords: triglyceridy; Silver; Double bond positional isomers; vysokoúčinná kapalinová chromatografie; Temperature; Triglycerides; Regioisomers; Chromatography, High Pressure Liquid; Trans isomers; teplota; Silver-ion HPLC; stříbro; Triacylglycerol